Alternative Options for Sewage Sludge Treatment and Process Improvement Through Circular Patterns: LCA-based Case Study and Scenarios - Mellino, Salvatore; Protano, Gaetano; Buonocore, Elvira; Angelis, Giuseppe De; Liu, Gengyuan; Xu, Linyu; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
In the pursuit of more sustainable wastewater treatment (WWT) processes, life cycle assessment (LCA) can be used as a valuable tool to evaluate the environmental impacts associated to WWT plants. In this study LCA is applied to compare the environmental performance of three scenarios for sludge disposal in a WWT plant located in southern Italy. The first business-as-usual scenario is based on the actual sludge management performed within the case-study plant: after mechanical treatment, dewatered sludge is transported by truck to a landfill for final disposal. The second scenario assumes a circular pattern, with anaerobic fermentation of sludge to biogas, and biogas use for electricity and heat cogeneration: electricity is feedback to WWT, while heat is used for digestate drying, in addition to thermal energy from previously recovered waste cooking oil (WCO). The third scenario suggests an improved circular pat-tern where the dried sludge is further gasified for syngas production and syngas is added to biogas for heat and electricity production. Scenario results suggest that increased circularity through recycling would be capable of reducing both the contribution to environmental impact categories and the fossil energy consumption up to 50%.